2021
DOI: 10.22219/jamanika.v1i4.19435
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Financial Ratios on Growth Profit in Manufacturing Industry Sector Companies Listed on the Indonesia Stock Exchange

Abstract: This research aims to find out the effect of financial ratio to profit growth on manufacturing industry companies or processing industries listed on the Indonesia Stock Exchange in 2016-2019. Purposive sampling techniques were obtained by 13 companies. The analysis used in this study is multiple linear regression analysis. The results in this study found that the current ratio partially positively affects profit growth, quick ratio partially positively and significantly affects profit growth, debt asset ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
1
1
Order By: Relevance
“…This study aligns with previous research by Suyono et al (2019) and Firman & Salvia (2021) stating that total asset turnover doesn't significantly influence profit growth. However, it contrasts with studies Gunawan & Wahyuni (2013), Endri et al (2020) , andFakhruddin et al (2021) suggesting that total assets turnover has a positive and significant impact on profit growth. Additionally, this finding contradicts research by Purwitasari & Soekotjo (2019) dan Suciana & Hayati (2021) which indicate that total assets turnover has a significant negative impact on profit growth.…”
Section: The Effect Of Total Asset Turnover (Tato) On Profit Growthcontrasting
confidence: 83%
See 1 more Smart Citation
“…This study aligns with previous research by Suyono et al (2019) and Firman & Salvia (2021) stating that total asset turnover doesn't significantly influence profit growth. However, it contrasts with studies Gunawan & Wahyuni (2013), Endri et al (2020) , andFakhruddin et al (2021) suggesting that total assets turnover has a positive and significant impact on profit growth. Additionally, this finding contradicts research by Purwitasari & Soekotjo (2019) dan Suciana & Hayati (2021) which indicate that total assets turnover has a significant negative impact on profit growth.…”
Section: The Effect Of Total Asset Turnover (Tato) On Profit Growthcontrasting
confidence: 83%
“…The quick ratio, which is used to determine how well a company can meet its current obligations with its current assets-aside from inventory-is called that (Kasmir, 2018:138). Due to research by Fakhruddin et al (2021), indicates that the quick ratio has a positively and considerable impact on profit growth. However, Dini et al (2021) observed that profit growth was significantly and negatively affected by the quick ratio.…”
Section: Introductionmentioning
confidence: 99%
“…8, 2023:865-886 al., (2020) juga menemukan bahwa Current Ratio (CR) memiliki pengaruh positif dan signifikan terhadap pertumbuhan laba di perusahaan perdagangan dan jasa. Penelitian tersebut sejalan dengan Fakhruddin et al, (2021) yang juga memperoleh hasil bahwa Current Ratio (CR) memiliki pengaruh positif dan signifikan terhadap pertumbuhan laba pada perusahaan manufaktur. Current Ratio (CR) merupakan rasio yang mengukur likuiditas perusahaan dengan aktiva lancar.…”
Section: Gambar 2 Kerangka Konseptualunclassified
“…Predictive information about profit growth is needed because the company's profit growth in the future cannot be ascertained. One of the tools to measure profit growth is financial ratios (Fakhruddin et al, 2021) where to assess the performance of a company based on existing financial data in the company's financial statements can use financial ratios as an analytical tool.…”
Section: Introductionmentioning
confidence: 99%